The philosophy of the daily prayer in Islamic source texts - Halilović Tehran (Kom: Časopis za Religijske Nauke, 2022)
The most significant and comprehensive form of service to God among Muslims is the daily prayer (Ar. salah; Persian. namaz). The daily prayer introduces discipline into the spiritual life not only of individuals but also of the Muslim society. The physical and conceptual components of the daily prayer reveal various aspects of the significance of this ritual in Islam. In this paper, we explore the philosophy of the daily prayer and its essence due to which the prayer is required by Sharia law. Deeper understanding of the daily prayer presented in Islamic source texts represents prayer as a gradual and comprehensive developmental path of the soul, which is all the more necessary for the believer, the higher his spiritual position. Performing daily prayer together in mosques is strictly recommended in Islamic traditions. Cultural activities originating from religious gatherings manifest the social aspect of the daily prayer. As the knowledge of the essence of the prayer is more deeply rooted among believers, the presence of religious culture is more pronounced in common prayers even beyond that time. The daily prayer is an Islamic identity that is constantly displayed in the life of Muslim believers. The interpretation of the essence of the daily prayer as a ritual that lasts only a few minutes a day stems from insufficient knowledge of Islamic Sharia. The subject of this paper is based on the rational interpretation of Sharia regulations, which is why we are methodologically more committed to the original Islamic texts and ideas of representatives of rational scientific disciplines in Islam. The study of the purposes and intentions of Sharia precepts has a long and rich tradition among Muslim scholars.